Trimannose-coupled antimiR-21 for macrophage-targeted inhalation treatment of acute inflammatory lung damage - Christina Beck; Deepak Ramanujam; Paula Vaccarello; Florenc Widenmeyer; Martin Feuerherd; Cho-Chin Cheng; Anton Bomhard; Tatiana Abikeeva; Julia Schädler; Jan-Peter Sperhake; Matthias Graw; Seyer Safi; et al. (Nature Communications, 2023)
Abstract Recent studies of severe acute inflammatory lung disease including COVID-19 identify macrophages to drive pulmonary hyperinflammation and long-term damage such as fibrosis. Here, we report on the development of a first-in-class, carbohydrate-coupled inhibitor of microRNA-21 (RCS-21), as a therapeutic means against pulmonary hyperinflammation and fibrosis. MicroRNA-21 is among the strongest upregulated microRNAs in human COVID-19 and in mice with acute inflammatory lung damage, and it is the strongest expressed microRNA in pulmonary macrophages. Chemical linkage of a microRNA-21 inhibitor to trimannose achieves rapid and specific delivery to macrophages upon inhalation in mice. RCS-21 reverses pathological activation of macrophages and prevents pulmonary dysfunction and fibrosis after acute lung damage in mice. In human lung tissue infected with SARS-CoV-2 ex vivo, RCS-21 effectively prevents the exaggerated inflammatory response. Our data imply trimannose-coupling for effective and selective delivery of inhaled oligonucleotides to pulmonary macrophages and report on a first mannose-coupled candidate therapeutic for COVID-19.